Natural frequencies measured from ambient vibration response of the arch dam of Mauvoisin. - Darbre, G.R.
The resonance frequencies of the 250 m high arch dam of Mauvoisin are obtained by way of ambient vibration tests. It is observed that the resonance frequencies initially increase with rising water level and then decrease with a further rise. This is linked to the two competing features of increasing entrained mass of water (reduction of the resonance frequencies) and of dam stiffening due to closing of the vertical construction joints (augmentation of the resonance frequencies). The ambient vibration test results are complemented by those obtained during earthquakes at an array of 12 accelerographs.
Keywords: Dams; Dynamics; Resonance frequencies; Ambient vibrations